The Ecology of Seashores - Knox, George (CRC Press, 2009)
Read it Online! The Ecology of Seashores explores the complex shore environment. It covers the ways in which representative species have adapted to life in a constantly changing environment in terms of their interactions, the control of community structure, and how energy and materials are cycled in different ecosystems. Written by an eminent marine biologist, this work emphasizes ecological processes and the use of systems analysis in understanding such processes. He gives complete coverage of the ecology of all seashore types: rocky shores, soft shores, sandy beaches, and estuaries at an advanced level. When appropriate, the author uses the energy circuit language of symbols and diagrams developed by H.T. Odum as a basis of understanding. The first comprehensive review and synthesis of the research on shore ecosystems, the book lends order to some of the most complex ecosystem types and presents a wide range of geographical examples. If you are involved in researching or managing coastal zones, The Ecology of Seashores provides exhaustive coverage of the essential background information you need.